Sources of Mohammed Moftaah's Methodology Cognitive A Study of Epistemological Bias (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research is based on the study of sciences upon which Mohammed Moftaah's methodology depends as a source of cognitive and tributary, which is outside the scope of literary criticism; and that is through the access to the structure of this methodology and analyze its scientific composition. The intended aim of this research is the access to the most important pillars of the Epistemology of this critic, and the detection of an important aspect in the critical construction which has not been studied yet. These sciences are: logic, mathematics, geometry, physics, biology, sociology, and information technologies. The methodology of this research is based on the extraction of the practical and the theoretical science that Moftaah has. and then making it an apparent and theorized substance , which says That Moftaah has succeeded at some of these sciences such as, , biology, Geometry, and some of them is based on formalism such as, mathematics, information technologies.